Immune regulation of islet homeostasis and adaptation. (1st April 2020) - Guo, Jinglong; Fu, Wenxian
Abstract: The islet of Langerhans produces endocrine hormones to regulate glucose homeostasis. The normal function of the islet relies on the homeostatic regulations of cellular composition and cell–cell interactions within the islet microenvironment. Immune cells populate the islet during embryonic development and participate in islet organogenesis and function. In obesity, a low-grade inflammation manifests in multiple organs, including pancreatic islets. Obesity-associated islet inflammation is evident in both animal models and humans, characterized by the accumulation of immune cells and elevated production of inflammatory cytokines/chemokines and metabolic mediators. Myeloid lineage cells (monocytes and macrophages) are the dominant types of immune cells in islet inflammation during the development of obesity and type 2 diabetes mellitus (T2DM). In this review, we will discuss the role of the immune system in islet homeostasis and inflammation and summarize recent findings of the cellular and molecular factors that alter islet microenvironment and β cell function in obesity and T2DM.